Analysis of Financial Performance Assessment Based on Common Size of Agricultural Sector Companies Listed on The Indonesian Stock Exchange 2018-2022 - Haris Maulana; Yan Widi Nugraha; Sasi Ngatiningrum; Edozi Putra; Nardi Sunardi (Indonesian Development of Economics and Administration Journal, 2023)
This study aims to analyze the company's financial performance of agricultural companies listed on the Indonesia Stock Exchange using Common Size analysis in the 2018-2022 period in terms of balance sheet and income statement. The type of research used is descriptive research with a quantitative approach. The source of data used in this study is a secondary source in the form of agricultural company financial statement documents from 2018 to 2022 with Common Size or percentage analysis per component. The results showed that financial performance using common size analysis in agricultural sector companies in 2018 to 2022 in terms of countries, three companies allocated and for assets mostly from debt (liabilities) and three companies allocated funds for assets from their capital to increase the margin of safety for creditors and strengthen the company's financial position. Common size in terms of the income statement, four companies are experiencing an increase in their net profit so that the company's financial performance is getting better and one other company has a poor financial performance because it has decreased in its net income.